2019
DOI: 10.1080/10428194.2018.1564827
|View full text |Cite
|
Sign up to set email alerts
|

Divergent LAG-3 versus BTLA, TIGIT, and FCRL3 expression in Sézary syndrome

Abstract: In S ezary syndrome (SS) impaired T-cell function and cytokine profile lead to immune evasion. Immune checkpoints non-redundantly regulate immune responses and targeting them is promising. We evaluated the expression of BTLA, CTLA-4, FCRL3, LAG-3, and TIGIT in tumor and nontumor SS T-cells.Compared to CD4þ T helper cells from ten healthy individuals, tumor cells of eight SS patients had a significant upregulation of BTLA (1.5-fold; p < .0001), FRCL3 (2.2-fold; p < .0028) and TIGIT (2.2-fold; p < .0003) express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
3
14
1
Order By: Relevance
“…However, as the combination of anti-PD-1 (nivolumab) with anti-CTLA-4 showed no benefit compared to nivolumab alone [116], there are no active or recruiting clinical studies testing the efficacy of CTLA-4 targeting in CTCL. A recent analysis [115] of a panel of checkpoint inhibitors in a small cohort of SS patients revealed a significant upregulation of FRCL3 and TIGIT expression, which is in line with the previous reports [117,118], together with a reduced expression of LAG-3 on CD4+ tumor cells. As several advanced clinical studies address TIGIT as a target molecule, it may also be of interest in CTCL.…”
Section: Immune Checkpoint Inhibitorssupporting
confidence: 89%
See 1 more Smart Citation
“…However, as the combination of anti-PD-1 (nivolumab) with anti-CTLA-4 showed no benefit compared to nivolumab alone [116], there are no active or recruiting clinical studies testing the efficacy of CTLA-4 targeting in CTCL. A recent analysis [115] of a panel of checkpoint inhibitors in a small cohort of SS patients revealed a significant upregulation of FRCL3 and TIGIT expression, which is in line with the previous reports [117,118], together with a reduced expression of LAG-3 on CD4+ tumor cells. As several advanced clinical studies address TIGIT as a target molecule, it may also be of interest in CTCL.…”
Section: Immune Checkpoint Inhibitorssupporting
confidence: 89%
“…In an analysis of CTCL skin samples, Querfeld et al [53] observed a higher expression of CTLA-4 on both CD4+ and CD8+ T cells. In another study no significant differences were found in CTLA-4 expression in CD4+ malignant versus bystander T cells in SS patients and healthy controls [115]. However, as the combination of anti-PD-1 (nivolumab) with anti-CTLA-4 showed no benefit compared to nivolumab alone [116], there are no active or recruiting clinical studies testing the efficacy of CTLA-4 targeting in CTCL.…”
Section: Recent Advances In Immunotherapies Of Ctclmentioning
confidence: 99%
“…In an analysis of skin samples, Querfeld et al observed higher expression of CTLA-4 on both CD4+ and CD8+ T cells. In our study, we observed no significant differences in CTLA-4 expression in CD4+ malignant vs. by-stander T cells in SS patients and healthy controls [188]. There is only a limited amount of data reports on the use of anti-CTLA-4 in CTCL.…”
Section: Primary Cutaneous Lymphomascontrasting
confidence: 52%
“…[61][62][63][64][65][66] However, the exact role of PD-1 and its two known ligands, PD-L1 and PD-L2, in the tumor microenvironment of patients with CTCL is not fully understood and may differ from those in tumors arising from non-T cells. 36,37,42,43,[61][62][63][64][65][66][67][68] A recent single-arm, multicenter phase II study showed an overall response of 38% to pembrolizumab in patients with relapsed/refractory MF and SS (stages IB-IV; n = 24). Six out of nine responders had ≥90% improvement in skin disease as determined by mSWAT score.…”
Section: Discussionmentioning
confidence: 99%